TaZAT8, a C2H2‐ZFP type transcription factor gene in wheat, plays critical roles in mediating tolerance to Pi deprivation through regulating P acquisition, ROS homeostasis and root system establishment. Issue 3 (9th June 2016) - Ding, Weiwei; Wang, Yanxia; Fang, Weibo; Gao, Si; Li, Xiaojuan; Xiao, Kai
Abstract : Transcription factors (TFs) play critical roles in mediating defense of plants to abiotic stresses through regulating downstream defensive genes. In this study, a wheat C2H2‐ZFP (zinc finger protein) type TF gene designated as TaZAT8 was functionally characterized in mediating tolerance to the inorganic phosphate (Pi)‐starvation stress. TaZAT8 bears conserved motifs harboring in the C2H2‐ZFP type counterparts across vascular plant species. The expression of TaZAT8 was shown to be induced in roots upon Pi deprivation, with a Pi concentration‐ and temporal‐dependent manner. Overexpression of TaZAT8 in tobacco conferred plants improved tolerance to Pi deprivation; the transgenic lines exhibited enlarged phenotype and elevated biomass and phosphorus (P) accumulation relative to wild‐type (WT) after Pi‐starvation treatment. NtPT1 and NtPT2, the tobacco phosphate transporter (PT) genes, showed increased transcripts in the Pi‐deprived transgenic lines, indicative of their transcriptional regulation by TaZAT8. Overexpression analysis of these PT genes validated their function in mediating Pi acquisition under the Pi deprivation conditions. Additionally, the TaZAT8 ‐overexpressing lines also behaved enhanced antioxidant enzyme (AE) activities and enlarged root system architecture (RSA) with respect to WT. Evaluation of the transcript abundance of tobacco genes encoding AE and PIN proteins, including NtMnSOD1, NtSOD1, NtPOD1;2, NtPOD1;5, NtPOD1;6, and NtPOD1;9, and NtPIN1 and NtPIN4 are upregulated in the TaZAT8 ‐overexpressing lines. Overexpression of NtPIN1 and NtPIN4 conferred plants to enlarged RSA and elevated biomass under the Pi‐starvation stress conditions. Our investigation provides insights into plant adaptation to the Pi‐starvation stress mediated by distinct ZFP TFs through modulation of Pi acquisition and cellular ROS detoxicity.